Atypical coverage in community-acquired pneumonia after outpatient beta-lactam monotherapy. (August 2017) - van Werkhoven, Cornelis H.; van de Garde, Ewoudt M.W.; Oosterheert, Jan Jelrik; Postma, Douwe F.; Bonten, Marc J.M.
Abstract: Introduction: In adults hospitalized with community-acquired pneumonia (CAP) after >48 h of outpatient beta-lactam monotherapy, coverage of atypical pathogens is recommended based on expert opinion. Methods: In a post-hoc analysis of a large study of CAP treatment we included patients who received beta-lactam monotherapy for >48 h before hospitalization. Length of hospital stay (LOS), 30-day mortality, and number of treatment escalations were compared for those that continued beta-lactam monotherapy and those that received atypical coverage at admission. Results: Of 179 patients (median age 66 years (IQR 50–78), 100 (56%) male), 131 (73%) received additional atypical coverage at admission. These patients were younger, had less comorbidities, and longer symptom duration, compared to those that continued beta-lactam monotherapy. In crude analysis, median (IQR) LOS was 6 (4–8) and 6 (4–9) days, mortality was 2% and 4%, and treatment escalations occurred in 8 (17%) and 11 (8%) patients without and with atypical coverage, respectively. Adjusted effect ratios for absence of atypical coverage on LOS, mortality, and treatment escalation were 0.77 (95% CI 0.61–0.97), 0.37 (0.04–3.67), and 2.75 (0.94–8.09), respectively. Conclusion: In adults hospitalized with CAP after >48 h of outpatient beta-lactam monotherapy, not starting antibiotics with atypical coverage was associated with a trend towards more treatment escalations, without evidence of increased LOS or mortality. Highlights: 8% of CAP patients are admitted after >48 h outpatient beta-lactam monotherapy. Of these, in 27% atypical coverage was not added at admission. Patients without atypical coverage had 17% later treatment escalations versus 8%. No atypical coverage was not associated with increased length of stay or mortality.